Financial Technology: An Analysis of the Financial Performance and Growth of Banking Companies - Fajri, Mega Barokatul; Rochmah, Sofi Machmudatul; Putro, Guruh Marhaenis Handoko; Lailiyah, Elliv Hidayatul; Zulyanti, Noer Rafikah; Syah, Imran (BALANCE: Economic, Business, Management and Accounting Journal, 2024)
The presence of financial technology provides opportunities for banking sector companies to develop innovative products and services. The rapid development of technology means that fintech services are considered an extension of banks. On the other hand, fintech banking, such as mobile banking and Internet banking, provides many conveniences, including serving Indonesian people who the traditional financial industry cannot serve. This research aims to test and analyze whether financial technology (independent variable) can influence company performance regarding ROA, ROE, NIM, BOPO, and company growth (dependent variable) in the banking industry. All banking companies listed on the IDX except Sharia banking are the data samples used. The testing method used is through the Between-Subjects Effect MANOVA test. This test shows that fintech positively affects ROA, ROE, and NIIM. However, the BOPO and company growth variables cannot be influenced by fintech.